PEMBERIAN TRAMPOLIN BASED SSC DAN CORE STABILITY DALAM PENINGKATAN KEMAMPUAN FUNGSIONAL ANAK DOWN SYNDROME - Waskito, Dinyoga Bima; Wijianto, Wijianto; Salma Muazarroh,; Christine Viola, (Journal of Innovation Research and Knowledge, 2023)
Background: Down syndrome (DS) is a common condition caused by trisomy of human chromosome 21. Clinical manifestations include hypotonia, poor posture control, abnormal movement, heart abnormalities, and respiratory function, which hinder functional ability. Down syndrome management interventions can use Trampolin based SSC and core stability exercise. Method: This case study uses a pre- and post-test research design by comparing assessments before and after Trampolin based SSC and core stability exercise interventions, then observed and evaluated for 4 meetings. Results: There was an increase in functional ability measured using GMFM from dimension C to dimension D. Conclusion: This case study concludes that physiotherapy intervention has an influence on the functional ability of patients with Down syndrome.